(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Evaluation of the status of prenatal screening and diagnosis of Down syndrome Subjects and methods: Retrospective, cross-sectional descriptive study on 33 fetuses and 73 children diagnosed with Down syndrome at Center for prenatal and neonatal diagnostic and screening – Nghe An Obstetrics and Pediatrics Hospital from 7/2020 to 7/2022 Results: Fetal ultrasound is a common prenatal screening method, providing the indication for prenatal diagnosis (amniocentesis). There were 2/33 (6%) fetus of Down syndrome with normal fetal ultrasound but positive Trisomy 21 NIPT. Amniocentesis implemented after 20 weeks had 6/33 (18,2%) cases. In 73 Down syndrome children: 15/73 (29.5%) cases with abnormalities on fetal ultrasound were recorded when information was collected from the family; screening by maternal blood (Double test/Triple test/NIPT) was performed in 11/73 cases, accounting for 15.1%. Conclusion: Combining maternal serum screening/NIPT with periodic ultrasound (under the guidance of the Ministry of Health) would help early prenatal diagnosis of DS. Raising awareness about prenatal screening and diagnosis for families in Nghe An and surrounding areas is an extremely vital issue.